Sosialisasi Revolusi Industri 4.0 Bagi Siswa SMA Negeri 1 Panga - Nurhaslita Sari; Marlizar, Desi; Macella, Agatha Debby Reiza; Kesha, Cut Nabilla; Mardhatillah, Muntaha; Handayani, Sri Wahyu (Pencerah, 2023)
In facing the era of the industrial revolution 4.0, education is needed to form a creative, innovative generation. This can be achieved one way by optimizing the use of technology as an educational aid that is expected to be able to produce outputs that can follow or change the times for the better. The purpose of the socialization of the association of the industrial revolution 4.0 with education among students of Panga I Public High School is so that among students understand the connection of the 4.0 revolution with education, students can utilize technology for ease of learning. The process of conducting this socialization was carried out using the lecture and discussion method of the material presented. The lecture was conducted to explain the understanding of the industrial revolution 4.0, the benefits of technology, the impact of changes from the industrial revolution 4.0. The lecture method is combined with utilizing laptop and LCD media to display power point material regarding the role of students in facing the industrial revolution 4.0. The results of the socialization link between the 4.0 revolution and education where students were very enthusiastic in listening to the socialization so that participants from among the students understood the connection of the 4.0 revolution with education, so they could utilize technology as supporting education. Besides that the target participants of the socialization activities of the role of students in facing the industrial revolution 4.0 almost met the target of 30 students. This number shows that almost all students of the school participated in this socialization activity. Submission of material can be delivered properly through the use of LCD. Overall the objectives of the socialization can be achieved well.